Real-world insights from acute management of potassium disorders in diabetic ketoacidosis - Zhang, Yue; Li, Jing; Deng, Shanshan; Zhang, Yongjing; Guo, Manli; Jiang, Fangfang; Luo, Lingguang; He, Yanqing; Ma, Shaogang; Peng, Yigen (Frontiers in Endocrinology, 2025)
BackgroundDiabetic ketoacidosis (DKA) is a severe hyperglycemic emergency characterized by metabolic acidosis and electrolyte disturbances. The optimal strategy for potassium replenishment in DKA remains incomplete. This study comprehensively characterized potassium disturbances in DKA and evaluated the effectiveness of potassium replenishment strategies, with a focus on the risk of hypokalemia during treatment.MethodsIn this multicentre retrospective cohort study, we enrolled the consecutive DKA patients admitted to seven tertiary centres across eastern, central and western China (1 January 2021–31 December 2023). Demographics, biochemical parameters and daily potassium chloride (KCl) replenishment were extracted and evaluated. We used multivariable logistic regression to identify predictors of hypokalaemia during treatment, internally validated the model, and constructed a practical nomogram.ResultsA total of 571 eligible subjects were included in the analysis. On admission, blood glucose, arterial pH, HCO3-, and electrolyte profiles were seriously deteriorated. Among the patients, 95 patients (16.6%) were hypokalemic, 352 (61.6%) normokalemic and 124 (21.7%) hyperkalemic. Hyperkalemia was more frequent in severe DKA and associated with renal impairment and the severity of DKA (p < 0.05). During treatment, 388 (67.9%) patients developed hypokalemia, the proportion rose to 73.6% among severe DKA cases. The occurrence of hypokalemia during treatment was independently associated with potassium concentration, HbA1c, and arterial pH at admission (p < 0.05). The statistical model predicted the risk of hypokalemia during treatment. A daily 6.0 g KCl supplement offered superior predictive efficacy for hypokalemia compared to lower doses throughout the treatment course.ConclusionsPotassium imbalances were highly prevalent in DKA. Although hyperkalemia was more common on admission, hypokalemia frequently developed during treatment. Daily 6.0 g KCl replenishment was superior to lower doses in predicting hypokalaemia. This study provided the full spectrum of potassium disorders in DKA and delivered an evidence-based, patient-specific replenishment framework.